Politik Hukum Siber dalam Mewujudkan Keamanan Ruang Digital Nasional - Wulandari, Laely (Fakultas Hukum Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2025)
This study aims to: (1) analyze the direction and construction of cyber legal policy in Indonesia in realizing national digital space security, and (2) assess existing cyber legal policies in providing legal protection against developing cyber threats. This research is a normative legal research with a statutory, conceptual, and analytical approach. The legal material for this research is obtained from primary, secondary, and tertiary legal materials. The analysis is conducted using legal theories, legal principles, and legal interpretations in the form of grammatical, systematic, and teleological interpretations. All legal materials are processed using legal reasoning that is coherent and systematic, and conclusions are drawn deductively. The results of the study indicate that the direction of cyber legal policy emphasizes the role of the state in regulating, protecting, and securing the national digital space, with a focus on electronic system security, data protection, and legal certainty. Existing regulations have formed a normative legal protection framework, but strengthening harmonization between laws, uniformity of interpretation, and institutional coordination are still needed so that legal protection can function optimally in facing the dynamics of cyber threats.